Reflections on the training management evaluation of the higher basic education professors in Ecuador - Camilo Enrique Rivadeneira Rivadeneira; Silvia Maribel Sarmiento Berrezueta; Maria de los Angeles Reyna González (Centro Provincial de Información de Ciencias Médicas, 2016)
Evaluation of the training management of the higher basic education professors in Ecuador is in a deep transformation process to elevate the quality. Taking into account the nonexistence of an evaluation system as fundamental component, in this study new theoretical and practical contributions aimed at improving this evaluative system are suggested.